2018
DOI: 10.1002/jbt.22024
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid mitigates arsenic‐trioxide‐induced mitochondrial dysfunction and cytotoxicity in SH‐SY5Y cells

Abstract: In the current study, neuroprotective significance of ellagic acid (EA, a polyohenol) was explored by primarily studying its antioxidant and antiapoptotic potential against arsenic trioxide (As O )-induced toxicity in SH-SY5Y human neuroblastoma cell lines. The mitigatory effects of EA with particular reference to cell viability and cytotoxicity, the generation of reactive oxygen species, DNA damage, and mitochondrial dynamics were studied. Pretreatment of SH-SY5Y cells with EA (10 and 20 μM) for 60 min follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…A study found that ellagic acid and punicalagin directly reduce ROS level produced by mitochondria . Ellagic acid was shown to exert an antioxidative effect via ameliorating mitochondrial dysfunction in concanavalin‐induced liver damage, gentamicin‐induced oxidative stress, and arsenic‐trioxide‐induced cytotoxicity in the human neuroblastoma cell line SH‐SY5Y . Cao et al .…”
Section: Mechanism Analysis Of Lipid Metabolism Regulated By Pomegranatementioning
confidence: 99%
“…A study found that ellagic acid and punicalagin directly reduce ROS level produced by mitochondria . Ellagic acid was shown to exert an antioxidative effect via ameliorating mitochondrial dysfunction in concanavalin‐induced liver damage, gentamicin‐induced oxidative stress, and arsenic‐trioxide‐induced cytotoxicity in the human neuroblastoma cell line SH‐SY5Y . Cao et al .…”
Section: Mechanism Analysis Of Lipid Metabolism Regulated By Pomegranatementioning
confidence: 99%
“…Ellagic acid has been shown to specifically induce apoptosis in cancer cells [13, 14, 18, 3034] while having cytoprotective activity in non-transformed cells [2, 4, 10, 12, 19, 35]. To determine whether EA activated apoptotic pathways, we measured caspase-3 catalytic activities in cells treated with EA for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…In non-transformed cells, EA is protective against oxidative insults [1012]. In contrast, EA has anti-proliferative and apoptotic effects in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ellagic acid has been shown to specifically induce apoptosis in cancer cells [13,14,18,[30][31][32][33][34] while having cytoprotective activity in non-transformed cells [2,4,10,12,19,35]. To determine whether EA activated apoptotic pathways, we measured caspase-3 catalytic activities in cells treated with EA for 24 hours.…”
Section: Ellagic Acid Is Not a Robust Inducer Of Caspase Activationmentioning
confidence: 99%
“…The number of cellular processes purported to be modulated by EA is impressive (Garcia-Nino and Zazueta, 2015). In non-transformed cells, EA is protective against oxidative insults (Sepand et al, 2016;Dhingra et al, 2017;Firdaus et al, 2018). In contrast, EA has anti-proliferative and apoptotic effects in cancer cells.…”
Section: Introductionmentioning
confidence: 99%